Evaluation of three remineralizing agents on surface roughness of enamel. - Vian O. Majeed; Hemn M. Sarmamy; Rebin A. Mohammedamin (Erbil Dental Journal)
Background and Objective: This study aimed to assess and compare, in vitro, the efficacy of Casien phosphopeptide-Amorphous calcium phosphate fluoride (CPP-ACP F), Sodium fluoride (NaF) mouth rinse and orthokin tooth paste in treatment of white spot lesions (WSLs) by examining changes in surface roughness of the enamel teeth following pH cycling. Methods: This in vitro experimental study was conducted on Forty (N=40) extracted sound maxillary premolars which were extracted for orthodontic purposes. Each tooth was soaked in demineralizing solution at 37oC for14 days to produce a white spot lesion. Then samples were coded from 1 to 40 for identification purposes and middle of buccal surface were subjected to profilometric analysis for obtaining enamel surface roughness parameters prior to any treatment (1st roughness recording). Afterward, specimens were randomly divided into four groups of 10 teeth. Each group was immersed and kept in an artificial saliva solution. In group 1 Specimens were treated with ortho kin toothpaste, in group 2 samples were immersed in 10 ml of 0.05% NaF mouthwash, every specimen in group 3 (control group) was immersed in 10ml artificial saliva and in group 4 specimens were treated with MI Paste Plus. After completion of 14 days application of remineralizing agents, a new assessment of enamel surface roughness was obtained by using profilometeric analysis. Results: The enamel surface roughness of all specimens was decreased after remineralization. There was a statistically significant difference between the roughness measured before and after the application of an experiment in GC group and ortho Kin group. The results showed that both Group 4 (GC, MI paste) and Group 2 (Mouth wash) group had a significant effect on the surface roughness when compared to other two groups. However, the remineralizing effect of Group 1 (Kin toothpaste) and control group were not significant. Conclusions: Within the limitations of this in vitro study, the results showed that MI Paste Plus and NaF are effective for the treatment of WSLs. Although Kin toothpaste had an efficacy superior to artificial saliva, its remineralizing effect seems to be inconsistent.